Noble Residences in the 15 th century Hungarian Kingdom: The Castles of Várpalota, Újlak and Kisnána in the Light of Architectural Prestige Representation - Nagy, Szabolcs Balázs (Dissertationes Archaeologicae, 2020)
Abstract of PhD thesis submitted in 2019 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of István Feld.